La spiritualité au miroir de l’ultramodernité - David Bisson (Amnis)
This article intends to highlight the topic of the transformation of the religious throughout the modern era using two different biases. First of all, by examining how the idea of religion takes root into the context of the “ultramodernity”, which is qualified by the acceleration of the modernity and makes it necessary to reconsider the concept of secularization. Then, we must also try to grasp a new way of understanding the term “spirituality” which would allow us to understand the new means of access to transcendence. Consequently, we will suggest a more precise definition of the spirituality before confronting it with certain sociological realities: “Spiritual Path” and “Holistic Spirituality”. To conclude, we willquestion the concept of “spirituality” according to what Yves Lambert named a “tournant axial”, in other terms: a general reconfiguration of the religious world.